2010
DOI: 10.1111/j.1476-5381.2010.00967.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of µ‐opioid receptors and block of KIR3 potassium channels and NMDA receptor conductance by l‐ and d‐methadone in rat locus coeruleus

Abstract: BACKGROUND AND PURPOSEMethadone activates opioid receptors to increase a potassium conductance mediated by G-protein-coupled, inwardly rectifying, potassium (KIR3) channels. Methadone also blocks KIR3 channels and N-methyl-D-aspartic acid (NMDA) receptors. However, the concentration dependence and stereospecificity of receptor activation and channel blockade by methadone on single neurons has not been characterized. EXPERIMENTAL APPROACHIntracellular and whole-cell recording were made from locus coeruleus neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 30 publications
(49 reference statements)
4
20
0
2
Order By: Relevance
“…The greater than predicted potency difference based on binding affinity at the higher stimulus intensity could reflect the d -isomer acting as a lower efficacy agonist relative to the l -isomer. This is consistent with whole cell current- and voltage-clamp recordings which showed a greater intrinsic activity for l -methadone relative to d -methadone (Matsui and Williams, 2010). However, further testing with combinations of the two isomers will be required to demonstrate definitively that, consistent with these in vitro assays, d -methadone functions as a partial efficacy μ agonist in vivo.…”
Section: Discussionsupporting
confidence: 89%
“…The greater than predicted potency difference based on binding affinity at the higher stimulus intensity could reflect the d -isomer acting as a lower efficacy agonist relative to the l -isomer. This is consistent with whole cell current- and voltage-clamp recordings which showed a greater intrinsic activity for l -methadone relative to d -methadone (Matsui and Williams, 2010). However, further testing with combinations of the two isomers will be required to demonstrate definitively that, consistent with these in vitro assays, d -methadone functions as a partial efficacy μ agonist in vivo.…”
Section: Discussionsupporting
confidence: 89%
“…CTb-488 was chosen as the retrograde tracer because of the high specificity of transport and the bright label provided by this compound (Conte et al, 2009). In addition, previous studies have shown that detection of fluorescently tagged CTb labeling is compatible with immunohistochemical techniques (Matsui and Williams, 2010). CTb-488 was infused into POR using the following coordinates with respect to lambda (in mm): +0.5, −0.1 anteroposterior, ±0.4 lateral and −4.4, −3.8 ventral from the skull surface, based on previous studies (Bucci et al, 2000; Burwell and Hafeman, 2003) and on the rat brain atlas of Paxinos and Watson (2007).…”
Section: Methodsmentioning
confidence: 94%
“…Estimates of agonist efficacy to determine RAVE values will be dependent on the effector under study. In addition, secondary actions of agonists such as the block of potassium channels by high concentrations of methadone will affect accurate determinations of efficacy Matsui and Williams, 2010). Likewise, the development of tolerance varies considerably with the assay.…”
Section: B Biased Agonism and M-opioid Receptor Regulationmentioning
confidence: 99%